Aedes aegypti(Linnaeus) larvae from dengue outbreak areas in Selangor showing resistance to pyrethroids but susceptible to organophosphates - Leong, Cherng Shii; Vythilingam, Indra; Wong, Meng Li; Wan Sulaiman, Wan Yusoff; Lau, Yee Ling (Elsevier, 2018)
The resistance status of Selangor Aedes aegypti (Linnaeus) larvae against four major groups of insecticides (i.e., organochlorines, carbamates, organophosphates and pyrethroids) was investigated. Aedes aegypti were susceptible against temephos (organophosphate), although resistance (RR 50 = 0.21–2.64) may be developing. The insecticides susceptibility status of Ae. aegypti larvae were found heterogeneous among the different study sites. Results showed that Ae. aegypti larvae from Klang, Sabak Bernam and Sepang were susceptible against all insecticides tested. However, other study sites exhibited low to high resistance against all pyrethroids (RR 50 = 1.19–32.16). Overall, the application of synergists ethacrynic acid, S.S.S.- tributylphosphorotrithioate and piperonyl butoxide increased the toxicity of insecticides investigated. However, the application failed to increase the mortality to susceptible level (>97%) for certain populations, therefore there are chances of alteration of target site resistance involved. Biochemical assays revealed that α-esterase, (Gombak, Kuala Langat, Kuala Selangor and Sabak Bernam strains) β-esterase (Klang and Sabak Bernam strains), acetylcholinesterase (Kuala Selangor and Sabak Bernam strains), glutathione-S-transferase (Kuala Selangor and Sabak Bernam strains) and mono-oxygenases (Gombak, Hulu Langat, Hulu Selangor and Kuala Langat strains) were elevated. Spearman rank-order correlation indicated a significant correlation between resistance ratios of: DDT and deltamethrin (r = 0.683, P = 0.042), cyfluthrin and deltamethrin (r = 0.867, P =0.002), cyflyuthrin and lambdacyhalothrin (r = 0.800, P =0.010), cyfluthrin and permethrin (r = 0.770, P =0.015) deltamethrin and permethrin (r = 0.803, P =0.088), propoxur and malathion (r = 0.867, P = 0.002), malathion and temephos (r = 0.800, P = 0.010), etofenprox and MFO enzyme (r = 0.667, P =0.050). The current study provides baseline information for vector control programs conducted by local authorities. The susceptibility status of Ae. aegypti should be monitored sporadically to ensure the effectiveness of current vector control strategy in Selangor.